2010
DOI: 10.1007/s00404-010-1354-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic laparoscopy in chronic pelvic pain

Abstract: Clinical examination and ultrasonography has a sensitivity of 8.1 and 2%, respectively. Laparoscopy helps in detecting many causes of CPP which clinical methods and ultrasonography fail to identify. This enforces the position of laparoscopy as a gold standard in evaluation of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 8 publications
0
29
0
1
Order By: Relevance
“…Laparoscopy, the current 'gold standard' for the investigation of CPP, can only identify dilated pelvic veins in the laparoscopic field of view and cannot produce objective measures of dilatation and tortuosity. 27 Laparoscopy is performed in the supine position, which causes decompression of the varices simply by gravity while the pneumoinflation of the peritoneal cavity during laparoscopy may cause further venous deflation. Although it has been suggested that a swift reverse of the laparoscopy table tilt from head-down to a head-up position will result in a rapid distension of the OV if reflux is present, this may not be possible or practical in the operating theatre.…”
Section: Diagnosismentioning
confidence: 99%
“…Laparoscopy, the current 'gold standard' for the investigation of CPP, can only identify dilated pelvic veins in the laparoscopic field of view and cannot produce objective measures of dilatation and tortuosity. 27 Laparoscopy is performed in the supine position, which causes decompression of the varices simply by gravity while the pneumoinflation of the peritoneal cavity during laparoscopy may cause further venous deflation. Although it has been suggested that a swift reverse of the laparoscopy table tilt from head-down to a head-up position will result in a rapid distension of the OV if reflux is present, this may not be possible or practical in the operating theatre.…”
Section: Diagnosismentioning
confidence: 99%
“…Similarly Razia Iftikar showed 56.6% endometriosis followed by pelvic adhesion in 16.6%, 6.6% benign ovarian cyst and PCOD 14 . Sharma D et al showed that commonest fi nding on laparoscopy was adhesions in 40%, endometriosis in 18%, and pelvic congestion syndrome in 20% 15 . Similarly in a study done by Chhetri S, diagnostic laparoscopy was able to detect pathology in 45 (81.8%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…The laparoscopic approach makes not only the detection but also the treatment of the underlying pathology of the pelvic pain feasible [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%